2014
DOI: 10.1038/cdd.2014.162
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of astrocyte-neuron cholesterol cross talk affects neuronal function in Huntington’s disease

Abstract: In the adult brain, neurons require local cholesterol production, which is supplied by astrocytes through apoE-containing lipoproteins. In Huntington's disease (HD), such cholesterol biosynthesis in the brain is severely reduced. Here we show that this defect, occurring in astrocytes, is detrimental for HD neurons. Astrocytes bearing the huntingtin protein containing increasing CAG repeats secreted less apoE-lipoprotein-bound cholesterol in the medium. Conditioned media from HD astrocytes and lipoprotein-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 63 publications
5
82
0
Order By: Relevance
“…Whereas some evidence points to dramatic downregulation of cholesterol in the brain [22, 44, 45], there also is evidence that, in spite of progressive reduction of brain cholesterol biosynthesis, steady-state levels of total cholesterol remain constant, suggesting compensatory mechanisms [21]. In support, a recent study reported that at least one precursor in the Bloch cholesterol synthetic pathway (desmosterol) is increased in R6/1 mice [31], thus supporting compensatory mechanisms to keep steady levels of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some evidence points to dramatic downregulation of cholesterol in the brain [22, 44, 45], there also is evidence that, in spite of progressive reduction of brain cholesterol biosynthesis, steady-state levels of total cholesterol remain constant, suggesting compensatory mechanisms [21]. In support, a recent study reported that at least one precursor in the Bloch cholesterol synthetic pathway (desmosterol) is increased in R6/1 mice [31], thus supporting compensatory mechanisms to keep steady levels of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…It is, for instance, known from the interactions of immune cells that inflammatory reactions may be dramatically boosted in feed-forward loops, and that they can therefore not be predicted from reactions of individual cells (Gantner et al 1996). Something similar may apply to the cycle of activated astrocytes affecting neurons and stressed neurons further activating astrocytes (Valenza et al 2015;Volterra and Meldolesi 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More recent research has shown that also non-neuronal cells may play a role in neurodegeneration. For instance, genetic or non-genetic alterations in astroglial cells may adversely affect the survival of neurons in models of human diseases related to the RETT syndrome, Huntington's disease, Parkinson's disease, multiple sclerosis, or amyotrophic lateral sclerosis (Gallardo et al 2014;Kohutnicka et al 1998;Lukovic et al 2015;Mayo et al 2014;Valenza et al 2015;Williams et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of astrocyte-mediated inflammatory signaling through TNFα enhanced motor function and reduced aggregates of mutant huntington in a mouse model of HD, suggesting anti-inflammatory treatments may help slow the progression of HD (Hsiao et al, 2014). Recent findings report that cholesterol biosynthesis by astrocytes is reduced in HD, leading to neuronal deficits (Valenza et al, 2015). Additionally, accumulation of huntington aggregates in astrocytes reduced astrocytes secretion of brain derived neurotrophic factor (BDNF) (Wang et al, 2012).…”
Section: Astrocytes In Neuropathologiesmentioning
confidence: 99%